APPLICATION OF THE DOUBLE SKIN FACADE CONCEPT IN AN EFFORT TO INCREASE THE THERMAL COMFORT OF IMAGE STUDIO ROOM - Maknun, Johar (Universitas Pendidikan Indonesia, 2020)
Abstrak- The development of technology in buildings is one of the factors triggering the acceleration of methods in the facade configuration system. Double Skin Facade (DSF) is one of the building facade concept innovations. The purpose of applying the DSF concept is to optimize the use of energy related to the air conditioning system to obtain thermal comfort in buildings. The results of measurements of the existing condition of the Image Studio room in the morning until 11.00 are included in the optimal comfort category, 11.00 - 13.00 are in the warm comfortable category and starting at 13.00-18.00 tend not to meet thermal comfort. Based on the simulation results the use of Double Skin Facade can reduce the temperature in the room around 3.47oC. With the application of Double Skin Facade in this Image Studio room, it can reduce the heat radiation from sunlight that directly enters through the window because it can be detained first in the double facade. The application of Double Skin Facade can increase the thermal comfort of an Image Studio room.Â Kata kunci- Double Skin FaÃ§ade, Thermal Comfort